2001
DOI: 10.1046/j.1532-5415.2001.4911239.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical Comorbidity and Rehabilitation Efficiency in Geriatric Inpatients

Abstract: Medical comorbidity was a significant predictor of rehabilitation efficiency in geriatric patients. Comorbidity scores >5 were prognostic of poorer rehabilitation outcomes and can serve as an empirical guide in estimating a patient's suitability for rehabilitation. Medical comorbidity predicted both the overall functional change achieved with retabilitation (Functional Independence Measure gains) and the rate at with which those gains were reached (rehabilitation efficiency ratio).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
2
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(93 citation statements)
references
References 27 publications
8
73
2
10
Order By: Relevance
“…6 Recent studies provide conflicting evidence regarding the factors that influence recovery in older adults with hip fracture after discharge from inpatient rehabilitation. Factors such as prefracture cognitive and functional status, 7,8 cognitive impairment, [9][10][11][12][13][14][15][16] age, 17 sex, [18][19][20] medical co morbidities, 21 and pain 22 have been found to influence recovery, function, and mobility outcomes over time in older adults after hip fracture, 12,[14][15][16] yet two systematic reviews indicated that individuals with cognitive impairment made gains that were similar to those of individuals without cognitive impairment. 16,23 Albeit informative, these studies were unclear as to how many individuals with complex needs were offered active rehabilitation, the type and approaches used during rehabilitation, and the extent to which inpatient care influenced long-term outcomes.…”
mentioning
confidence: 99%
“…6 Recent studies provide conflicting evidence regarding the factors that influence recovery in older adults with hip fracture after discharge from inpatient rehabilitation. Factors such as prefracture cognitive and functional status, 7,8 cognitive impairment, [9][10][11][12][13][14][15][16] age, 17 sex, [18][19][20] medical co morbidities, 21 and pain 22 have been found to influence recovery, function, and mobility outcomes over time in older adults after hip fracture, 12,[14][15][16] yet two systematic reviews indicated that individuals with cognitive impairment made gains that were similar to those of individuals without cognitive impairment. 16,23 Albeit informative, these studies were unclear as to how many individuals with complex needs were offered active rehabilitation, the type and approaches used during rehabilitation, and the extent to which inpatient care influenced long-term outcomes.…”
mentioning
confidence: 99%
“…En otros estudios, el promedio de los escores de esta escala variaba de acuerdo a la población estudiada. En un estudio canadiense 33 , que evaluó pacientes internados en unidad de rehabilitación geriátrica, el promedio de los escores fue 3,8, bastante próximo al valor observado en nuestro estudio. Adultos mayores en hospital general, o institucionalizados, presentan promedios más altos 13 .…”
Section: Sensibilidadunclassified
“…Indeed, somatic chronic comorbidities appear to have greater negative influence on the individual's decline in physical functions than expected [13]. In elderly people [14], comorbidities may negatively impact on the rehabilitation of patients, leading to smaller gains [15,16]. This aspect has been further investigated in COPD patients.…”
Section: Patient's Complexitymentioning
confidence: 99%